2016
DOI: 10.1002/hbm.23346
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic functional connectivity of neurocognitive networks in children

Abstract: The human brain is highly dynamic, supporting a remarkable range of cognitive abilities that emerge over the course of development. While flexible and dynamic coordination between different neural systems is firmly established for children, our understanding of brain functional organization in early life has been built largely on the implicit assumption that functional connectivity (FC) is static. Understanding the nature of dynamic neural interactions during development is a critical issue for cognitive neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
187
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 215 publications
(218 citation statements)
references
References 44 publications
28
187
1
2
Order By: Relevance
“…There is evidence that this property is important for executive functioning, learning, and switching between challenging task demands (Bassett et al, 2011; Braun et al, 2015; Chen et al, 2016). Over development, rs-fcMRI networks show increased within-subject variability (Hutchison and Morton, 2015; Marusak et al, 2016; Qin et al, 2015), consistent with EEG studies showing that signal complexity increases over development (McIntosh et al, 2008; Vakorin et al, 2011). Recent simultaneous EEG-fMRI work (Fransson et al, 2013) links developmental differences (infants versus adults) in rs-fcmri network dynamics with differences in EEG power spectra, consistent with the notion that temporal variability in very low frequency correlations is an emergent, hidden property of higher frequency power spectra (Chang et al, 2013; Tagliazucchi et al, 2012), which is known to change continuously throughout development (Miskovic et al, 2015; Rodriguez-Martinez et al, 2015; Smit et al, 2012; Whitford et al, 2007).…”
Section: Development Of Temporal Dynamicssupporting
confidence: 80%
“…There is evidence that this property is important for executive functioning, learning, and switching between challenging task demands (Bassett et al, 2011; Braun et al, 2015; Chen et al, 2016). Over development, rs-fcMRI networks show increased within-subject variability (Hutchison and Morton, 2015; Marusak et al, 2016; Qin et al, 2015), consistent with EEG studies showing that signal complexity increases over development (McIntosh et al, 2008; Vakorin et al, 2011). Recent simultaneous EEG-fMRI work (Fransson et al, 2013) links developmental differences (infants versus adults) in rs-fcmri network dynamics with differences in EEG power spectra, consistent with the notion that temporal variability in very low frequency correlations is an emergent, hidden property of higher frequency power spectra (Chang et al, 2013; Tagliazucchi et al, 2012), which is known to change continuously throughout development (Miskovic et al, 2015; Rodriguez-Martinez et al, 2015; Smit et al, 2012; Whitford et al, 2007).…”
Section: Development Of Temporal Dynamicssupporting
confidence: 80%
“…However, many works indicated that during the resting state, significant variations could be observed in a short time, and dynamic FC analysis has drawn more and more attention (Cai, Zhang, et al, 2018;Cai, Zille, et al, 2018;Damaraju et al, 2014;Hutchison et al, 2013;Marusak et al, 2017;Rashid et al, 2014). This suggests that both individual distinctiveness and cognitive prediction using the resting state fMRI are proven to be the most challenging for identifying individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Brain states can then be summarized as the patterns of connectivity at each centroid, and additional summary metrics such as the amount of time each subject spends in a given state can be computed. Using this definition of brain state, it has been shown that the patterns of connectivity describing each state are reliably observed across groups and individuals (Yang et al, 2014), while other characteristics such as the amount of time spent in specific states and the number of transitions between states vary with meaningful individual differences such as age (Hutchison and Morton, 2015; Marusak et al, 2017) or disease status (Damaraju et al, 2014; Rashid et al, 2014). However, this approach towards understanding what has recently been termed the “chronnectome” is still in its infancy (Calhoun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%